(untitled) (Collection of scientific works «Modern structures of metal and wood», 2019)
One of the important tasks in the field of metal structures improving is to reduce their material consumption, which can be achieved by further studying the actual work of structures, improving design schemes, developing a structural form, using high-strength steels, and using effective cross sections types of elements. In the article, the authors investigate the question of rational constructive solutions for the conveyor gallery of the grain handling terminal of the sea trade port. The length of designed conveyor gallery is 118.69 m and it consists of four spans (36, 18, 30, 30 m long) and five supports 5.86 m, 12.39 m, 15.65 m, 21.16 m, 26.68 m high, the gallery has a longitudinal grade of 12°. Gallery consists of the one temperature unit. At the same time, an existing handling station is adopted by a fixed support providing structural stability in the longitudinal direction, the remaining supports are adopted flat, allowing displacement in the longitudinal direction during temperature movements. A truss structure has been adopted among the various possible structural solutions for the span structure, as the most technologically advanced and easy to install. Spans are carried out according to a discontinuous design and consist of two flat supporting trusses with a height of 3.2 m with parallel belts and a triangular lattice with additional posts connected to each other in a three-dimensional space block with a width of 3.3 m by transverse beams of covering and overlapping, horizontal ties along the lower and upper truss belts and supporting frames at the ends having a rigid connection of the crossbar with the supporting posts of the supporting trusses. The loads acting on the gallery – erection load, technological, atmospheric, including episodic – seismic effects were found (the intensity of seismic impact was adopted 7 points, based on the data of the building area`s geotechnical conditions and in accordance with the class of responsibility of the construction object). Calculation of steel structures of the conveyor gallery was performed using the computer-aided engineering system SCAD. The sections of truss rods are designed with rectangular roll-welded slender hollow section, in accordance with the requirements of economy, reducing the complexity of manufacturing and corrosion resistance. The same profiles were also applied to other span elements – floor beams, roofs, and tie elements. Flat two-member supports with a single-plane diagonal connecting grid were designed. Cross- sections of the supports are designed in two versions – with the hot rolled I-beams №45 and alternatively from a composite light formed I-beam with a corrugated sinusoidal wall. The savings on all posts of conveyor gallery supports for the second version make 4.2 tons of steel.